Polymerization of Poly Methyl Methacrylate Using Emulsion Method and H2O2 as Initiator - Sari Purnavita; Cyrilla Oktaviananda; Sri Sutanti; Herman Yoseph Sriyana; Antonius Prihanto; Antonio Mafeli (Universitas Wahid Hasyim, 2022)
This study aims to study the effect of the amount of initiator (H2O2) on the viscosity of the Polymethyl Methacrylate (PMMA) emulsion and the solids content. The treatment of independent variables is H2O2 by 1%, 2%, 3%, and 4%. This research procedure was carried out in a two-stage process. The first stage is the process to separate the inhibitor contained in the methyl methacrylate monomer by adding a 1 N concentration of NaOH solution, stirring until evenly distributed, then put into a separating funnel to separate pure methyl methacrylate from the inhibitor dissolved in alkaline solution. The second stage is the polymerization reaction process using the emulsion method. Dissolve the poly vinyl alcohol in hot water at 70oC, put the poly vinyl alcohol solution into a three-neck flask, which is equipped with a stirrer and a hot plate heater, add the initiator and up to 60oC, then add the methyl methacrylate monomer with stirring and heating at room temperature 100oC for 1 hour. The resulting product is a thick poly methyl methacrylate emulsion, has a milky white color, and has good adhesion. Furthermore, the viscosity test was carried out using ford cup number 4 and the solids content test. The results showed that the more initiators added, the higher the viscosity and the higher the solids content.